2002
DOI: 10.1023/a:1014427615636
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Contrast sensitivity (CS) is often used to assess spatial and temporal vision in animals. Conventional behavioral psychophysical techniques are both time and labor intensive, whereas measurement of CS functions by means of the pattern electroretinogram (PERG) is considerably more rapid and efficient. Are the two methods comparable, however? To answer this question, contrast-sensitivity functions were obtained using both the PERG and behavioral psychophysics in the same subjects, which were White Carneaux pigeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Psychophysical investigations on human and vertebrate animals have shown that visual contrast sensitivity depends strongly on stimulus spatial frequency (SF) (Bisti and Maffei, 1974; Uhlrich et al, 1981; Hodos et al, 2002; Sowden et al, 2002; Jarvis and Wathes, 2008). Across species, the CSFs have a similar inverted-U shape with a single peak, although the spatial frequency domain varies in different species and the peak of the CSF shifts slightly with stimulus size and luminance (Uhlrich et al, 1981; Jarvis and Wathes, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical investigations on human and vertebrate animals have shown that visual contrast sensitivity depends strongly on stimulus spatial frequency (SF) (Bisti and Maffei, 1974; Uhlrich et al, 1981; Hodos et al, 2002; Sowden et al, 2002; Jarvis and Wathes, 2008). Across species, the CSFs have a similar inverted-U shape with a single peak, although the spatial frequency domain varies in different species and the peak of the CSF shifts slightly with stimulus size and luminance (Uhlrich et al, 1981; Jarvis and Wathes, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the OKN response also involves midbrain processing. Hodos et al (2002) found that the contrast sensitivity function derived from pERG recordings in pigeons had a similar bandwidth and peak spatial frequency to that derived from psychophysical testing, but was lower by approximately 54%. The high-frequency cut-off derived from pERG recordings was also lower than that obtained by psychophysical testing, by 37% (Hodos, Ghim, Potocki, Fields & Storm, 2002).…”
Section: Discussionmentioning
confidence: 62%
“…Hodos et al (2002) found that the contrast sensitivity function derived from pERG recordings in pigeons had a similar bandwidth and peak spatial frequency to that derived from psychophysical testing, but was lower by approximately 54%. The high-frequency cut-off derived from pERG recordings was also lower than that obtained by psychophysical testing, by 37% (Hodos, Ghim, Potocki, Fields & Storm, 2002). In another study involving chickens, the pERG was used to measure and subsequently correct for refractive errors; peak pERG amplitudes were obtained with +6 to +10 D trial lenses interposed, corresponding to refractive errors of +3 to +7 D after accounting for the working distance (Kruse, Schwahn, Gekeler, Weiss & Schaeffel, 1999).…”
Section: Discussionmentioning
confidence: 62%
“…The ERG is a reliable diagnostic procedure for the early detection of affected dogs before the ophthalmoscopical abnormality becomes apparent [39]. The ERG is also used to diagnose inherited and nutritional photoreceptor degenerations in cats [22,36] as well as retinal disorders in a number of other species, uncluding chickens [5,34], pigeons [9], rabbits [11,33,35], sheep [12], and monkeys [4,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Even though most animals need to be under general anesthesia to properly measure ERG, various sedatives and anesthetics have been documented to affect ERG responses [10,15,16,27,38]. It is also important to be aware of species variation as to the suitable types and dose levels of anesthetics [9,13,33,34,36]. …”
Section: Introductionmentioning
confidence: 99%